조생 향찰벼 신품종 ‘향드림찰’ - 이종형(Jong-Hyeong Lee); 한상욱(Sang-Wook Han); 장정희(Jung-Hee Jang); 서재순(Jae-Soon Seo); 장재은(Jae-Eun Jang); 최병열(Byoung-Rourl Choi); 박인태(In-Tea Park); 김광호(Kang-Ho Kim) (Korean journal of breeding, 2017)
‘Hyangdreamchal’, a new early maturing, aromatic and glutinous rice variety was developed by the crop breeding team of Crop Research & Development Division, GARES, Hwaseong, Korea in 2012. ‘Hyangdreamchal’ was derived from a cross between ‘Jinbuchal’ and ‘Miyakaori’ in 2001. This variety headed on July 28 which was 14 days earlier than ‘Hwaseongbyeo’ in Gyeonggi Province. It showed resistance to lodging with strong culm. It's culm length and panicle length were 71 cm and 20 cm, respectively. This variety has 13 tillers per hill and 92 spikelets per panicle. It was medium grain variety and 1,000 grain weight of brown rice was 20.1g. Its cold tolerance was stronger than ‘Hwaseongbyeo’ however it was susceptible to blast virus disease, bacterial leaf blight and insect pest. The milled rice of ‘Hyangdreamchal’ had a glutinous and aromatic endosperm. The yield potential of ‘Hyangdreamchal’ in milled rice was 4.15 MT/ha under the ordinary culture of the local adaptability test in 4 areas of Gyeonggi Province for three years. This variety would be adaptable to the Gyeonggi Province. (품종보호번호 : 제5568호)